Expressions of p53 and PUMA in fibroblasts of systemic sclerosis patients are normal at transcription level. (14th September 2017) - Mahmoudi, Mohammad Bagher; Abed Khojasteh, Majid; Alsahebfosoul, Fereshteh; Gharibdoost, Farhad; Mostafaei, Shayan; Ganjalikhani‐hakemi, Mazdak; Mahmoudi, Mahdi
Summary: Background: Systemic sclerosis (SSc) fibroblasts show resistance apoptosis mechanisms, which enhances the fibrosis stage of the disease. Impaired function of p53 upregulated modulator of apoptosis (PUMA) has been related to deficits in p53‐dependant apoptosis pathway. This study aimed to evaluate the transcriptional levels of p53 and PUMA mRNAs in fibroblasts from SSc patients and compare it with healthy individuals. Methods: In this case‐control study, skin biopsy samples were obtained from 19 patients with diffuse cutaneous SSc (DcSSc) and 16 healthy controls. Afterward, dermal fibroblasts were isolated and cultured. After extraction of total RNA from cultured fibroblasts, complementary DNA (cDNA) was synthesized. mRNA quantification was carried out using real‐time PCR, SYBR Green PCR master mix, and specific primers for p53 and PUMA. Results: No significant alteration was observed in mRNA expression levels of p53 and PUMA ( P = .99 and .23, respectively) in fibroblasts from SSc patients compared with controls. Conclusions: Apoptosis pathways are impaired in fibroblasts from patients with SSc, leading to chronic fibrosis. Nonetheless, PUMA/p53 pathway may not be involved in dysfunction of apoptosis mechanisms in fibroblasts of patients with SSc.